2019
DOI: 10.5194/acp-2019-1006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative study between ground-based observations and NAVGEM-HA reanalysis data in the MLT region

Abstract: <p><strong>Abstract.</strong> Atmospheric waves are a key driving mechanism for the circulation in the Earth's atmosphere. Such waves covervarious spatial and temporal scales, e.g., planetary waves with periods of several days, atmospheric tides with periods of aninteger fraction of a day and gravity waves with periods ranging from minutes to several hours. In particular, atmospheric tidesgain large amplitudes at the Mesosphere/lower Thermosphere (MLT) region. Recently… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
(62 reference statements)
1
11
0
Order By: Relevance
“…For comparison with ground-based instruments, vertical profiles of NAVGEM-HA analyzed winds and temperatures are converted from the model vertical grid in geopotential altitude to a geometric altitude grid. To date, NAVGEM-HA winds and tides have been shown to be in good agreement with ground-based meteor radar observations (McCormack et al, 2017;Eckermann et al, 2018;Laskar et al, 2019;Stober et al, 2019) and with independent satellite-based wind observations as reported in Dhadly et al (2018). In the present study we employ NAVGEM-HA analyzed winds at 82.5 km altitude, staying below altitudes where sponge layer effects may impact the tides, to validate the method of extracting migrating tidal signatures from the SD meteor wind data.…”
Section: Navgem-hasupporting
confidence: 63%
“…For comparison with ground-based instruments, vertical profiles of NAVGEM-HA analyzed winds and temperatures are converted from the model vertical grid in geopotential altitude to a geometric altitude grid. To date, NAVGEM-HA winds and tides have been shown to be in good agreement with ground-based meteor radar observations (McCormack et al, 2017;Eckermann et al, 2018;Laskar et al, 2019;Stober et al, 2019) and with independent satellite-based wind observations as reported in Dhadly et al (2018). In the present study we employ NAVGEM-HA analyzed winds at 82.5 km altitude, staying below altitudes where sponge layer effects may impact the tides, to validate the method of extracting migrating tidal signatures from the SD meteor wind data.…”
Section: Navgem-hasupporting
confidence: 63%
“…Therefore, we cannot completely rule out aliasing from the lunar semidiurnal tide into modeled SW2 amplitudes and phases that were calculated using a Fourier decomposition of hourly TIME-GCM output. However, we suspect that the contribution from aliasing by the lunar semidiurnal tide into our calculated SW2 amplitudes and phases to be fairly small (see Stober et al, 2019). Nonetheless, we can assess to what extent the predominant semidiurnal wave forcing or SW2, differs between the three cases we have simulated (2012-2013 with and without GW and 2013-2014).…”
Section: Migrating Semidiurnal Tidementioning
confidence: 91%
“…Data from the Sodankylä meteor radar (SGO) used herein are available at https://www.sgo.fi/pub/JGR_SSW_2013https://www.sgo.fi/pub(cd to JGR_SSW_2013/HWD_201301 or JGR_SSW_2013/HWD_201401). Access to data from the CMOR and Collm meteor radars is discussed in Stober et al (2019). SABER atomic hydrogen data are available at http://saber.gats-inc.com/data.php then by clicking on the ftp://saber.gats-inc.com/Version2_0/Level2A/ link.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…A detailed summary of each system can be found in Table 2.1. The systems are well-known and have proven to provide reliable and continuous measurements for cross-validation (McCormack et al, 2017;Stober et al, 2019) or long-term change studies (Iimura et al, 2011;Jacobi et al, 2015;Wilhelm et al, 2019;Pancheva et al, 2020). In Figure 2.1, we present an overview of where each system is located.…”
Section: Meteor Radar Observationsmentioning
confidence: 99%
“…We applied a harmonized data processing to generate homogeneous wind time series for all sites. The wind retrieval is described in more detail in (Stober et al, 2018) and was validated against meteorological analysis NAVGEM-HA (Navy Global Environment Model -High Altitude) (McCormack et al, 2015;Stober et al, 2019). NAVGEM-HA meteorological analysis utilizes a sophisticated 4DVAR data assimilation scheme, which assimilates observations including mesospheric data from MLS and SABER (Kuhl et al, 2013;McCormack et al, 2015;Eckermann et al, 2018).…”
Section: Meteor Radar Observationsmentioning
confidence: 99%